2020
DOI: 10.1159/000505930
|View full text |Cite
|
Sign up to set email alerts
|

Modified Glasgow Prognostic Score and Carcinoembryonic Antigen Predict Poor Prognosis in Elderly Patients with Colorectal Cancer

Abstract: <b><i>Objective:</i></b> To investigate the prognostic values of the preoperative modified Glasgow Prognostic Score (mGPS) and carcinoembryonic antigen (CEA) alone and combined in elderly patients with colorectal cancer (CRC) planning to receive curative surgery. <b><i>Methods:</i></b> We retrospectively analyzed 130 elderly patients (aged ≥80 years) with CRC who received curative surgery between 2008 and 2016. The preoperative mGPS and CEA levels were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Various studies have shown that biomarkers such as PNI and NLR, which reflect systemic inflammation, are prognostic factors for malignancy [ 4 , 5 ]. The mGPS, derived from serum albumin and CRP levels, is among these biomarkers and is predictive of prognosis in CRC patients [ 6 ]. CAR, which is calculated from the ratio of serum albumin to CRP, has also been used as a prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that biomarkers such as PNI and NLR, which reflect systemic inflammation, are prognostic factors for malignancy [ 4 , 5 ]. The mGPS, derived from serum albumin and CRP levels, is among these biomarkers and is predictive of prognosis in CRC patients [ 6 ]. CAR, which is calculated from the ratio of serum albumin to CRP, has also been used as a prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of systemic inflammation in various carcinomas has been widely reported in recent years [ 2 , 3 ]. In addition, multiple biomarkers of systemic inflammation have been developed, including the prognostic nutritional index (PNI) [ 4 ], the neutrophil to lymphocyte ratio (NLR) [ 5 ], and the modified Glasgow Prognostic Score (mGPS) [ 6 ], all of which have been reported to be related to CRC prognosis. While mGPS uses C-reactive protein (CRP) and albumin levels, CRP to albumin ratio (CAR) is a calculated value developed by Fairclough et al [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The modi ed Glasgow Prognostic Score (mGPS) is a validated predictive model for systemic in ammatory response (SIR), calculated based on Creactive protein (CRP) levels representing the level of in ammation and albumin levels representing the nutritional status [9]. Numerous studies have shown that increased GPS or mGPS level indicates poor prognosis in patients with mCRC, lung, oesophageal, and gastric cancers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, elderly patients often present with different clinical features, including a greater proportion of advanced-stage disease at diagnosis, and a higher prevalence of comorbidities [ 5 ]. Last but not least, elderly patients with CRC undergoing surgery are more likely to have a poor prognosis and survival rates than younger patients [ 6 , 7 ]. Thus, it is necessary to identify new prognostic markers and explore the potential mechanism of poor prognosis in elderly patients with CRC, thereby improving their survival and leading to better management and treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%